Speech Act Analysis in the Short Story Bersiap Kecewa Bersedih Tanpa Kata-Kata - Syalaisha Renaisse Fathiha (CV Edukastra Mandiri, 2025)
In literary works, language is employed by authors as a medium to articulate ideas and thoughts, thereby creating interactions among characters that give rise to speech acts. This study examines the forms of locutionary, illocutionary, and perlocutionary speech acts found in Putu Wijaya’s short story Bersiap Kecewa Bersedih Tanpa Kata-Kata. The objective of this research is to describe the manifestations of speech acts based on the categories of locution, illocution, and perlocution as reflected in the short story. The research adopts a descriptive qualitative method. Data were collected using attentive listening, comprehension, and note-taking techniques. The findings indicate the presence of three types of speech acts: (1) locutionary speech acts, which involve stating something, encompassing declarative, interrogative, and imperative forms; (2) illocutionary speech acts, which involve performing an action through the force of utterance, comprising assertive, directive, expressive, commissive, and declarative types; and (3) perlocutionary speech acts, which influence the feelings, thoughts, and actions of the interlocutor